CEO turnover, firm performance and enterprise reform in China: evidence from new micro data - Takao Kato; Cheryl Long (Institute for the Study of Labor (IZA), 2006)
Using comprehensive financial and accounting data on China's listed firms from 1998 to 2002, augmented by unique data on CEO turnover, ownership structure and board characteristics, we estimate Logit models of CEO turnover. We find consistently for all performance measures including both stock return and various accounting measures that: (i) overall, CEO turnover is significantly and inversely related to firm performance though the magnitude of the relationship is modest; (ii) CEO turnover-performance link is stronger when the percentage of company shares owned by the largest shareholder is larger. Furthermore, insofar as stock performance is concerned, (iii) turnover-performance link is found to be weaker for listed firms still controlled by the state; (iv) the appointment of independent directors enhances turnover-performance link; (v) the listing suspension mechanism, i.e., the ST designation, adopted by China's securities regulatory agency appears to be effective in improving turnover-performance tie; and (vi) listed firms with CEOs holding additional positions in the controlling shareholders have weaker turnover-performance link. Consistent with the law and finance approach to corporate governance and the literature on economic transition, our findings suggest that any fundamental improvement in China's corporate governance will require a broad program that encompasses not only privatization but also laws and their effective implementation to provide better protection for investors.
Keywords: M52; M12; J33; P34; G30; O16; O53; G30; G15; 330; executive turnover; firm performance; enterprise reform; corporate governance; ownership structure; China; transition economies; Führungskräfte; Arbeitsmobilität; Börsenkurs; Wirtschaftsreform; China